VOICES OF THE SUBALTERN: DECODING RESISTANCE THROUGH SEMIOTICS IN COLLINS’THE BALLAD OF SONGBIRDS AND SNAKES - Callista Aulia Nugraha; Rahayu Puji Haryanti (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This article examines the forms of symbolic resistance posed by subaltern groups in Suzanne Collins' novel, The Ballad of the Songbirds and the Snakes (2020), through the application of Roland Barthes' semiotic theory and Gayatri Spivak's concept of subalternity. The narrative is set in the dystopian realm of Panem, characterized by a hierarchical system in which power is concentrated in the capital while the districts face systematic marginalization. The focus of this study is on how characters engage in symbolic acts of defiance through the mediums of song, performance, and myth. By employing a qualitative textual analysis, the research interprets significant symbols such as the mockingjay, snakes, and folk songs as complex sign systems that articulate resistance against hegemonic power. Each of these symbols is explored through denotative, connotative, and mythical lenses to reveal how they operate within the storyline to echo the genuine, albeit subtle, resistance efforts of marginalized groups. The findings indicate that, despite the constraints imposed by oppressive systems, subaltern individuals are capable of asserting their agency via coded language, emotional influence, and acts of performative subversion. By integrating semiotic analysis with postcolonial critique, this study illustrates the capacity of literature to serve as a platform for expressing subaltern challenges and resilience through symbolic expression.